The Incidence Rate and the Effects of Progressive Muscle Relaxation on Fatigue, Muscle Pain, and Sleep Quality Among Coffee Farmers - Loda, Yohana Jawe; Ratu, Jacob Matheos; Muntasir, Muntasir (Malikussaleh University, Aceh, Indonesia, 2025)
Farmers frequently endure exhaustion and muscle aches as a result of their heavy labour, which affects their sleep quality and health. Farmers' occupational health is improved by using gradual muscle relaxation to minimize fatigue, muscle pain, and poor sleep quality. The goal of this study is to see how common muscular relaxation is and how effective it is at reducing fatigue, muscle pain, and improving sleep quality among coffee producers in Bajawa District. This research employs two different designs: descriptive observational research with a cross-sectional design and experimental design with pretest and posttest designs. A total of 240 farmers were sampled using stratified random sampling, while 18 farmers were sampled using multistage random sampling. The findings of this study using descriptive analysis revealed that fatigue, muscle pain, and sleep quality were all high among coffee farmers in Bajawa District, with 119 people (49.6%) reporting severe fatigue, 124 people (51.7%) reporting high muscle pain, and 160 people reporting poor sleep quality (66.67 %). The paired t-test yielded a p-value=0.000, indicating that administering ROP had an effect on farmer tiredness (p0.05), muscle pain (p0.05), and sleep quality (p0.05). ROP, in conclusion, has a tiredness impact that relieves fatigue, calms and comforts the environment, manages pain, and induces sleep.